An analysis of creative economy and its determinants in Thailand compared to selected developed and developing countries - Samuch Oupala; Juthathip Jongwanich; Zimmermann, Willi; Winai Wongsurawat; Royal Thai Government; Asian Institute of Technology Fellowship (2020)
Purpose {u2013} The purpose of this research is to analyze factor influencing creative goods exports as well as the effect of creative goods exports using Thailand and other East and Southeast Asian economies as case studies. Methodology {u2013} Extended Gravity model is modified to determine the factors influencing creative goods exports. The panel data model is employed to examining such relationship. In addition, Endogenous Growth model is implemented to capture effect of creative goods exports on Thailand and other East and Southeast Asian economic growth. Findings {u2013} The key determinants of creative goods exports are GDP per capita, distance, education and R&D expenditure of trading partners. Moreover, creative goods exports could positively stimulate economic growth in Thailand. However, the magnitude of such positive impacts in Thailand is lower than that in developed economies in East and Southeast Asia, such as South Korea, Hong Kong, Japan and Singapore, but it is higher than that in developing countries in Southeast Asia nation. Implication {u2013} Expansion of creative goods is one of the crucial elements in promoting economic growth in Thailand. However, comparing to other high-income countries in East and Southeast Asian countries, creative goods exports has contributed less to economic growth in the country. To promote creative goods exports, improving GDP per capita is necessary. R&D expenditure needs to be prioritized, along with promoting education. These two are the crucial elements in stimulating GDP per capita. In addition, well manage macroeconomic environment is essential to move a country to higher income level, which eventually helps promote creative goods exports.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2020
Keywords: Developing countries -- economics -- Thailand; Economics -- Developing countries -- Sociological aspects